Selective auditory grouping by zebra finches: testing the iambic–trochaic law - Spierings, Michelle (Anim Cogn, 2017)
Humans have a strong tendency to spontaneously group visual or auditory stimuli together in larger patterns. One of these perceptual grouping biases is formulated as the iambic/trochaic law, where humans group successive tones alternating in pitch and intensity as trochees (high–low and loud–soft) and alternating in duration as iambs (short–long). The grouping of alternations in pitch and intensity into trochees is a human universal and is also present in one non-human animal species, rats. The perceptual grouping of sounds alternating in duration seems to be affected by native language in humans and has so far not been found among animals. In the current study, we explore to which extent these perceptual biases are present in a songbird, the zebra finch. Zebra finches were trained to discriminate between short strings of pure tones organized as iambs and as trochees. One group received tones that alternated in pitch, a second group heard tones alternating in duration, and for a third group, tones alternated in intensity. Those zebra finches that showed sustained correct discrimination were next tested with longer, ambiguous strings of alternating sounds. The zebra finches in the pitch condition categorized ambiguous strings of alternating tones as trochees, similar to humans. However, most of the zebra finches in the duration and intensity condition did not learn to discriminate between training stimuli organized as iambs and trochees. This study shows that the perceptual bias to group tones alternating in pitch as trochees is not specific to humans and rats, but may be more widespread among animals.